Analisis Penggunaan Pantun dalam Budaya Masyarakat Gayo Lues - Susi Susanti; Rajab Bahry; Mohd Harun (JIM Pendididikan Bahasa dan Sastra Indonesia, 2019)
This research is entitled about “Analysis of the Use of Rhyme in the Culture of the Gayo Lues Community” the problem in this study is how te use of rhyme in the culture of the Gayo Lues community?. The purpose of this study was to describe the use of rhyme in the culture of the Gayo Lues community. The source of the data from this study is the Gayo Lues native community in the form of oral data obtained from informants namely pantun Gayo related to the culture of Gayo Lues. Data collection techniques in this study used interview techniques, records, notes, and dokumentation. While the data anlysis tecniqueis done by data colection, data classification, and data presentation. After the data analysis was carried out, it was found that the final end of the study, namely the culture of the Gayo Lues community in Blangkejeren District, Gayo Lues District, which uese rhyme there are seven cultures, namely (1) saman dance, (2) dance bines, (3) didong jalu (didong fight), (4) young man, (5) marriage, (6) speech/lecture, and (7) advise children